Interferon‐alpha, immune activation and immune dysfunction in treated HIV infection. Issue 2 (28th February 2014) - Cha, Lilian; Berry, Cassandra M; Nolan, David; Castley, Allison; Fernandez, Sonia; French, Martyn A
Abstract : Type I interferons (IFNs) exert anti‐viral effects through the induction of numerous IFN‐stimulated genes and an immunomodulatory effect on innate and adaptive immune responses. This is beneficial in controlling virus infections but prolonged IFN‐α activity in persistent virus infections, such as HIV infection, may contribute to immune activation and have a detrimental effect on the function of monocytes and T and B lymphocytes. Activation of monocytes, associated with increased IFN‐α activity, contributes to atherosclerotic vascular disease, brain disease and other 'age‐related diseases' in HIV patients treated with long‐term antiretroviral therapy (ART). In HIV patients receiving ART, the anti‐viral effects of IFN‐α therapy have the potential to contribute to eradication of HIV infection while IFN‐α inhibitor therapy is under investigation for the treatment of immune activation. The management of HIV patients receiving ART will be improved by understanding more about the opposing effects of IFN‐α on HIV infection and disease and by developing methods to assess IFN‐α activity in clinical practice.